Filozofova sociološka avantura: družboslovna prizadevanja Joséja Ortege y Gasseta - od kulturno-filozofske publicistike do poskusa utemeljevanja sociologije - Sruk, Vida (2009)
Philosophier's Sociological Adventure: the Social Sciences Efforts of José Ortega y Gasset - from Cultural and Philosophical Journalism to the Attempt to Justify Sociology. No abstract.